Epidermolysis bullosa simplex with pyloric atresia and muscular dystrophy. - Papastavros, V.; Nathoo, R.; Wangia, M. (European Journal of Pediatric Dermatology, 2016)
Epidermolysis bullosa simplex with pyloric atresia (EBS-PA) and EBS with muscular dystrophy (EBS-MD) are rare subtypes of EBS; cases of these two subtypes are both welldocumented in the literature and due to plectin (PLEC) gene mutations inherited in an autosomal recessive pattern. However, there is only one prior report of a single infant with EBS complicated by both muscular dystrophy and pyloric atresia. We report the case of a newborn female who presented with diffuse mucocutaneous blistering, bowel obstruction, hypoplastic features and poor muscular tone diagnosed with EBS with muscular dystrophy and pyloric atresia secondary to deleterious plectin mutations. This case highlights the association between plectin changes and expression of both phenotypes in a single individual.